The Effect of Block System on Learning Interest of 11th Grade Students of ULP SMKN 9 Bandung - Ramadhan, Rizal Rizky; Gitasiswhara, Gitasiswhara; Wulung, Shandra Rama Panji (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
This study examines the effect of the SMK learning block system on the learning interest of 11th grade ULP students with a Classroom Action Research (PTK) approach. Starting from the description of the block system learning and student interest in learning when the learning model takes place. with quantitative descriptive methods through simple linear regression data processing to determine the value of the influence of the vocational learning block system variable on student interest in learning Data collection is carried out through classroom observations, filling out questionnaires to students, and interviews with teachers as well as the curriculum vice-secretary and human resources (HR) bidand. This research is located at SMKN 9 Bandung , West Java. The results showed that there is no influence between the block system and students' interest in learning, there are other stronger factors that affect the interest in learning of students in class XI of the ULP.